Used Durables and Online Buying: An Attitudinal Study of Indian Youth - Kar, Surjit Kumar; Bhoi, Monalisa (Indian Journal of Marketing, 2014)
The present paper is an empirical paper based on an online survey conducted in the first quarter of the year 2013. Preliminary findings were presented at an international conference in the last quarter of 2013, and changes were made based on suggestions received from the co-delegates. The study attempts to investigate the attitude, perception, and motivation of Indian youth, especially management students, regarding their adoption of a distinguished selling/ buying online platform for used laptops through a consumer to consumer discount e-commerce portal. With an exploratory research design, this paper uses multivariate analyses to draw perceptual mapping of the proposed portal vis-Ã -vis other e-commerce sites. It simulates a business model with an integrated value chain from acquisition and selling of used laptops at a discounted price to a value added after sales/ post purchase service in a committed manner. A focus group discussion was carried out initially among the sampling units from the sampling frame of a management college to understand the antecedents. Based on the findings, a questionnaire was developed and pre-tested through a survey design. Across its two stages, the research used both exploratory and descriptive design in sequence. The second part of the research helps in conceptualizing an optimum marketing mix, and explaining differentiation and positioning variables for the commercial launch of such a venture. However, the current paper discusses only the first part of the study.